A Novel MSCRAMM Subfamily in Coagulase Negative Staphylococcal Species - Arora, Srishtee; Uhlemann, Anne-Catrin; Lowy, Franklin D.; Hook, Magnus (Frontiers in Microbiology, 2016)
Coagulase negative staphylococci are important opportunistic pathogens. Staphylococcus epidermidis, a coagulase negative staphylococcus, is the third leading cause of nosocomial infections in the US. Surface proteins like Microbial Surface Components Recognizing Adhesive Matrix Molecules (MSCRAMMs) are major virulence factors of pathogenic gram positive bacteria. Here, we identified a new chimeric protein; SesJ in S. epidermidis, which represents a prototype of a new subfamily of MSCRAMMs. Structural predictions show that SesJ has structural features characteristic of a MSCRAMM along with a N-Terminal repeat region and an Aspartic acid containing repeat region, features that have not been previously observed in staphylococcal MSCRAMMs but have been found in other surface proteins from gram positive bacteria. We identified and analyzed structural homologs of SesJ in three other coagulase negative staphylococci. These homologs of SesJ have an identical structural organization but varying sequence identities within the domains. Using flow cytometry, we also show that SesJ is expressed constitutively on the surface of a representative S. epidermidis strain, from early exponential to stationary growth phase. Thus SesJ is positioned to interact with protein targets in the environment and play a role in S. epidermidis virulence.